Emotional Responses to Aesthetically Integrated and Standard Subtitles in a Fantasy-Thriller Audiovisual Context - Leveridge, Francesca; Mevel, Pierre-Alexis; Tsikandilakis, Myron (Journal of Audiovisual Translation, 2024)
Situated at the intersection of Psychology, Film studies, Accessibility Studies and Translation Studies, this article investigates the emotional correlates of two types of subtitles (standard and aesthetically integrated) on audiences in the context of fear-eliciting clips with Russian fantasy thriller Night Watch (Bekmambetov, 2004). Our experiment employed a methodology combining electrodermal activity (EDA), heart-rate responses (HR) and self-reports (questionnaires) to account for the complex interplay between experiential, cognitive, behavioural and physiological elements that make up emotional responses. We examined the psychophysiological and self-report responses to two subtitling delivery effects – standard subtitles and aesthetically integrated subtitles – focussing specifically on fear. We used significance-testing and Bayesian analyses to compare the two subtitling deliveries. For both analyses, we found that the presentation of aesthetically integrated subtitles led to higher positively rated psychophysiological arousal and quality of viewing experience ratings compared to standard subtitles. This novel finding suggests that aesthetically integrated subtitles could be the future of audiovisual translation. Lay Summary This study explored how different types of subtitles affect how our viewing experience and how we feel while watching films. The researchers showed clips one might consider emotionally arousing/scary from a Russian film (Night Watch, a 2004 film by Timur Bekmambetov) in three different ways: no subtitles, regular subtitles displayed at the bottom of the screen, and artistic subtitles that blended in with the film’s visual language and story. In our article, we call these subtitles ‘aesthetically integrated subtitles’. The researchers measured how people reacted physically (sweat glands activity, faster heart rate) and asked - using questionnaires - the participants about their viewing experience and how emotionally aroused/scared they felt. Interestingly, the participants who watched the clips with the aesthetically integrated subtitles responded with higher positively rated physiological arousal and also reported that the experience was more emotionally arousing/scary and enjoyable. This suggests that aesthetically integrated subtitles could provide a new way to translate or create films that are more accessible and emotionally engaging for viewers.